Outcome of Opsoclonus with Neuroblastoma - J Gordon Millichap (Pediatric Neurology Briefs, 1994)
The neurologic and developmental outcomes in 10 children with opsoclonus-myoclonus (“dancing eyes syndrome”) and neuroblastoma were reviewed by examination of records at Northwestern University Medical School and Children’s Memorial Hospital, and the University of Illinois Hospital, Chicago.